DESCRIPTION OF KNOWLEDGE, ATTITUDES AND ACTIONS OF STUDENTS OF SD NEGERI BUENG CALA ON CLEAN AND HEALTHY LIVING BEHAVIORS - Ambia Nurdin; Zamzami; Muhammad; Bukhari; Murtadhahadi; Mohd Isa T. Ibrahim; Mahyuddin; Dewi Astini; Cut Megawati; Zahrul Fuadi; Mulyadi; Idal Bahri; Yunida Pangastuti (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2023)
Clean and healthy living behavior in schools is a set of behaviors that are practiced by students, teachers and the school community as learning outcomes, so that they are able to independently prevent disease, improve health and play an active role in creating a healthy environment. The aim of the study was to find out the description of the knowledge, attitudes and actions of class VI students at SD Negeri Bueng Cala towards clean and healthy behavior. This research is descriptivewith a sample of 57 respondents using the total sampling technique. The instrument used was a questionnaire in the form of a statement with a total of 24 statements, and the results of data analysis are presented intable form of frequency distribution and percentage.The results of this study indicate that the knowledge of class VI students at SD Negeri Bueng Cala regarding Clean and Healthy Behavior (PHBS) is in the high category, namely 31 respondents (54.39%). The attitudes of students regarding PHBS were in the positive category of 33 respondents (57.89%). The actions of students regarding PHBS were in the category of 32 respondents (56.14%). Based on the results of the research, it is hoped that students will be able to prevent disease, strengthen children's skills in clean and healthy living behavior, improve children's mental and social development, and improve students' abilities to protect themselves from harmful substances.